Optical Sensors and Sensing Congress (ES, FTS, HISE, Sensors) 2019
DOI: 10.1364/sensors.2019.sth5a.1
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Optical Fiber Sensors

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In summary, soft robots today are too expensive and lack a general fabrication platform, however, recent advances in drawing soft polymer fibres may provide solutions to these problems. It has been shown that soft polymers such as polyurethane can be thermally drawn down to extremely narrow tubes (fibers) at the scale of a few hundred microns [39][40][41]. More importantly, the process of mass producing these polymer tubes is far cheaper than those used for producing other soft robotic designs such as the bi-bellows actuator [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, soft robots today are too expensive and lack a general fabrication platform, however, recent advances in drawing soft polymer fibres may provide solutions to these problems. It has been shown that soft polymers such as polyurethane can be thermally drawn down to extremely narrow tubes (fibers) at the scale of a few hundred microns [39][40][41]. More importantly, the process of mass producing these polymer tubes is far cheaper than those used for producing other soft robotic designs such as the bi-bellows actuator [42,43].…”
Section: Introductionmentioning
confidence: 99%